Selective detection of hydrogen sulfide using copper oxide-doped tin oxide based thick film sensor array - Choudhary M.; Singh N.K.; Mishra V.N.; Dwivedi R. (My University, 2025)
In this work, copper oxide-doped (1, 3 and 5 wt%) tin oxide powders have been synthesised by sol-gel method and thick film sensor array has been developed by screen printing technique for the detection of H2S gas. Powder X-ray diffraction pattern shows that the tin oxide (SnO2) doped with 3 wt% copper oxide (CuO) has smaller crystallite size in comparison to 0, 1 and 5 wt% CuO-doped SnO2. Furthermore, field emission scanning electron microscopy manifests the formation of porous film consisting of loosely interconnected small crystallites. The effect of various amounts of CuO dopant has been studied on the sensing properties of sensor array with respect to hydrogen sulfide (H2S) gas. It is found that the SnO 2 doped with 3 wt% CuO is extremely sensitive (82%) to H2S gas at 150 C, while it is almost insensitive to many other gases, i.e., hydrogen (H2), carbon monoxide (CO), sulphur dioxide (SO2) and liquefied petroleum gas (LPG). Moreover, at low concentration of gas, it shows fast recovery as compared to response time. Such high performance of 3 wt% CuO-doped SnO2 thick film sensor is probably due to the diminishing of the p-n junction and the smallest crystallite size (11 nm) along with porous structure. © 2013 Elsevier B.V. All rights reserved.